Post-Pandemic Health Conditions and Influence of Twelve Weeks of Yogic Practices on Young to Middle-Aged Housewives in Rural and Urban Environments - Biswas, Subhashis; Kirtania, Tumpa; Saha, Gopal Chandra; Paul, Saptarshi; Rajak, Dilip Kumar (YCAB Publisher, 2025)
Background: The COVID-19 pandemic has precipitated adverse effects on the physical and mental health of young to middle-aged housewives residing in diverse rural and urban environments. Despite the widespread repercussions, there exists a paucity of research focused on elucidating the post-COVID health status of this specific demographic and the potential therapeutic merits associated with the integration of yogic practices into their daily lives. Objective: This study aims to scrutinize the post-Covid health status of young to middle-aged housewives and explore the potential advantages of integrating yogic practices within their routines. Methods: The study included sixty young to middle-aged housewives, thirty from rural and 30 from urban areas and categorised as rural controlled (n=15), rural experimental (n=15), urban controlled (n=15) and urban experimental (n=15).Both the experimental groups followed twelve weeks yogic practice protocol based on the Ministry of AYUSH's Common Yoga protocol. Results: Urban housewives exhibited a higher body mass index and a higher percentage of body fat. The yogic intervention had a significant effect on BMI (p = 0.02), muscular endurance (p = 0.002), and flexibility (p = 0.001) among rural young to middle-aged housewives. However, only improvement in flexibility (p = 0.0005) has been observed in urban young to middle-aged housewives. These outcomes highlight the potential positive impact of twelve-week yogic intervention in improving selected physical parameters of young to middle-aged housewives. Conclusion: The findings of the study emphasize the importance of yogic practice, into post-pandemic recovery efforts to promote optimal health and resilience in diverse populations. Further research is warranted to explore the long-term effects and sustainability of such interventions on overall health outcomes. Keywords: Covid-19; common yoga protocol; physical fitness; yoga; middle aged housewives